An Effective approach of Data Migration from Private to Public cloud using E-LSB with Improvisation Technique - Pallavi; Kumar, Dinesh (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing has recently became a most important and mainly discussed topic in the Technological industry. Almost all organizations use the Cloud, because it provides an easy and cost efficient way of using applications,which provides scalability for various systems. Still, it is not clear upto now how and when cloud computing should be used and where actually to be implemented. Existing applications are often written in such a way that it actually does not really fit a cloud environment well. Also, certain quality attributes like performance, security or portability integrity scalability network issues can be affected. Much more studies are actually needed on how existing systems should be used into the Cloud so that it can be transferred and it is checked what are the consequences of the migration. So in the proposed system we have developed an approach for enhancing the security of the data while migrating data on the cloud environment with the help of Cryptography and Stegnographic approach. In this mechanism, data is first entered or uploaded into the system and migrated on cloud.